1,4-Dipolar cycloaddition in organic synthesis: a facile route to isoquinoline fused heterocycles - Nair, Vijay; Sreekanth, Anakkalil R.; Abhilash, N.; Biju, Akkattu T.; Varma, Luxmi; Viji, Sreemathi; Mathew, Saumini (Arkivoc, 2005)
The three component condensation reactions involving isoquinoline, dimethyl acetylenedicarboxylate and carbonyl dipolarophiles such as o- and p-benzoquinones and Nsubstituted isatins constitute a one-pot synthesis of a variety of [1,3]oxazino isoquinoline derivatives via 1,4-dipolar cycloaddition.

Engaging zwitterions in carbon-carbon and carbon-nitrogen bond- forming reactions: a promising synthetic strategy - Nair, Vijay; Menon, Rajeev S.; Sreekanth, A. R.; Abhilash, N.; Biju, Akkattu T. (Accounts of Chemical Research, 2006)
An Account of carbon−carbon and carbon−nitrogen bond-forming reactions mediated by zwitterions generated by the addition of organic nucleophiles to activated unsaturated systems highlighting their synthetic potential is presented.